EPISTEMOLOGI PESANTREN: STUDI INTERPRETATIF TERHADAP MAKNA KITAB KUNING BAGI GURU DAN SANTRI - Imamuddin Yusup; Hanafiah Hanafiah; Faiz Karim Fatkhullah (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
Islamic boarding schools (pesantren) represent the oldest form of Islamic educational institutions in Indonesia and possess a distinctive epistemological system, which is particularly reflected in the tradition of kitab kuning (classical Islamic texts) learning. The kitab kuning function not only as primary sources of classical Islamic scholarship but also as media for the transmission of values, scholarly authority, and the formation of students’ character. This study aims to examine the epistemology of pesantren through an interpretative approach to the meaning of kitab kuning as perceived by teachers (kiai/ustaz) and students. Employing a qualitative research design with an interpretative–phenomenological method, data were collected through in-depth interviews, participant observation, and document analysis within the pesantren environment. The findings reveal that kitab kuning are understood as (1) sources of scholarly legitimacy and religious authority, (2) media for the internalization of Ahl al-Sunnah wa al-Jama‘ah (Aswaja) values, and (3) instruments for the formation of students’ intellectual and moral habitus. The epistemology of pesantren, as grounded in the kitab kuning tradition, emphasizes the integration of knowledge, ethics, and spirituality, thereby offering a holistic model of Islamic education that remains relevant amid the challenges of modernity. ABSTRAKPesantren merupakan lembaga pendidikan Islam tertua di Indonesia yang memiliki sistem epistemologi khas, terutama tercermin dalam tradisi pembelajaran kitab kuning. Kitab kuning tidak hanya berfungsi sebagai sumber rujukan keilmuan keislaman klasik, tetapi juga menjadi medium transmisi nilai, otoritas keilmuan, dan pembentukan karakter santri. Penelitian ini bertujuan untuk mengkaji epistemologi pesantren melalui pendekatan interpretatif terhadap makna kitab kuning bagi guru (kiai/ustaz) dan santri. Penelitian ini menggunakan pendekatan kualitatif dengan metode interpretatif-fenomenologis. Data diperoleh melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi di lingkungan pesantren. Hasil penelitian menunjukkan bahwa kitab kuning dimaknai sebagai (1) sumber legitimasi keilmuan dan otoritas religius, (2) media internalisasi nilai Aswaja, dan (3) sarana pembentukan habitus intelektual dan moral santri. Epistemologi pesantren yang berbasis kitab kuning menekankan integrasi antara pengetahuan, etika, dan spiritualitas, sehingga relevan sebagai model pendidikan Islam yang holistik di tengah tantangan modernitas.